2000
DOI: 10.1103/physrevb.62.3905
|View full text |Cite
|
Sign up to set email alerts
|

Universal conductance fluctuations and low-temperature1/fnoise in mesoscopic AuFe spin glasses

Abstract: We report on intrinsic time-dependent conductance fluctuations observed in mesoscopic AuFe spin-glass wires. These dynamical fluctuations have a 1/f -like spectrum and appear below the measured spin-glass freezing temperature of our samples. The dependence of the fluctuation amplitude on temperature, magnetic field, voltage, and Fe concentration allows a consistent interpretation in terms of quantum interference effects, that are sensitive to the slowly fluctuating spin configuration.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
(42 reference statements)
10
16
0
Order By: Relevance
“…Then S R ͑f͒ was measured while slowly cooling the system in constant H. The whole procedure was repeated for different values of H. Larger ͉H͉ generally resulted in lower temperatures for the onset of increased noise, similar to previous results on a standard metallic spin glass. 25 In the range of ͉H͉ Յ 4 T we confirm 14 that the changes in magnetoresistance are well under 1% and hence are irrelevant to the dramatic H dependence of the noise. The decrease in the noise onset T with increase in H roughly resembles theoretical predictions for the field-dependent T g ͑Ref.…”
Section: Results and Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…Then S R ͑f͒ was measured while slowly cooling the system in constant H. The whole procedure was repeated for different values of H. Larger ͉H͉ generally resulted in lower temperatures for the onset of increased noise, similar to previous results on a standard metallic spin glass. 25 In the range of ͉H͉ Յ 4 T we confirm 14 that the changes in magnetoresistance are well under 1% and hence are irrelevant to the dramatic H dependence of the noise. The decrease in the noise onset T with increase in H roughly resembles theoretical predictions for the field-dependent T g ͑Ref.…”
Section: Results and Analysissupporting
confidence: 52%
“…[10][11][12][21][22][23][24][25][26][27] Figures 1͑a͒ and 1͑b͒ show the dependence of S R ͑f͒ and noise-spectral slope ␣ ϵ − ‫ץ‬ ln S R ͑f͒ ‫ץ‬ ln͑f͒ on T. Above T Ϸ 6.5 K we found ordinary 1 / f-like ͑␣ Ϸ 1͒ noise with small temporal variations in the noise power. Around T Ϸ 6.5 K, S R ͑f͒ increases considerably and ␣ reaches its minimum ͑␣ Ϸ 0.5͒.…”
Section: Results and Analysismentioning
confidence: 99%
“…1 / f noise has intensively been studied for bulk and thin-film conductors, [9][10][11][12][13][14][15][16][17][18] in particular as a diagnostic tool for the technologically relevant electromigration ͑EM͒ mechanism. [19][20][21][22] Noise at low and high frequencies has also been explored in small constrictions, [23][24][25][26] nanoelectronic devices, 27,28 quantum point contacts, 29 submicron interconnects, 30,31 quantum coherent, quasiballistic and ballistic nanowires, [32][33][34][35][36][37][38][39] and tunneling contacts. 40,41 The power-spectral density of resistance fluctuations S R can phenomenologically be described by Hooge's law, 9,12 …”
Section: Introductionmentioning
confidence: 99%
“…Parallel to these theoretical developments, experimental measurements of conductance fluctuations in metallic spin glasses by de Vegvar et al [13] (see also [14]) demonstrated for the first time a clear signature of the spin glass freezing in the time-reversal antisymmetric part of the four terminal conductance. Later, several experiments focused on noise measurements in Cu:Mn [15] and Au:Fe [16] (see also [17] for similar studies in the doped semiconductor).…”
mentioning
confidence: 99%